Effect of Ionic Strength on the Kinetics of Oxidation of Ascorbic Acid by Methylene Green in Aqueous Methanol System - Saeed, Rehana; Razi Khan, Sameera; Ashfaq, Maria (Asian Journal of Chemistry, 2012)
The effect of ionic strength and temperature on the kinetics of the reaction between methylene green and ascorbic acid was studied in presence of iodine by spectrophotometric method. The oxidation of ascorbic acid was carried out in 10, 15, 20, 25 and 30 % aqueous methanol and decrease in the values of rate of reaction was observed with decrease in dielectric constant of solvent. The absorbance data was collected at 656 nm at different ionic strength and temperature ranges from 2.7063 × 10-4 mol dm-3 to 8.9604 × 10-4 mol dm-3 and 298 to 318 K with the difference of 5 K respectively. It was observed that with the increase in ionic strength and temperature the rate of the reaction also increased. The presence of iodine enhances the rate of chemical reaction. The reaction follows first order kinetics with respect to ascorbic acid and fractional order with respect to methylene green. The overall reaction is pseudo first order. Energy of activation (Ea*) was calculated with the help of kinetic data by using Arrhenius relationship. Thermodynamic parameters such as enthalpy change of activation (DH*), Gibbs free energy change of activation (DG*) and entropy change of activation (DS*) were also evaluated.